Dinuclear Metal Complexes, Part IX, Copper(II), Nickel(II) and Cobalt(II) Complexes with a Schiff-base Derived from-3-formylsalicylic Acid and Carbohydrazide - Satpathy, K.C.; Pandey, A.K.; Mahapatra, A.; Mishra, B. (Asian Journal of Chemistry, 2010)
Copper(II), nickel(II) and cobalt(II) complexes of the type [M (3-fsaH]2CAR(H2O)n] and [M2 (3-fsa)2-CAR(H2O)n] where (3-fsaH2)2-CAR is a Schiff-base derived from 3-formylsalicylic acid and carbohydrazide, n = 0, 1, 2 or 3 etc., have been isolated and characterised on the basis of physico-chemical methods. The antiferromagnetic character of dinuclear copper(II) complex has been revealed from the magnetic and ESR spectral data. The dinuclear cobalt(II) complex has been found to have a mixed-spin state comprising of a high-spin and a low-spin cobalt(II) ion. Also the dinuclear nickel(II) complex exhibits a slightly lower magnetic moment value corresponding to two unpaired electrons. The mononuclear copper(II) and cobalt(II) complexs are paramagnetic unlike the mononuclear nickel(II) complex. The reflectance spectra of all the complexes are consistent with the observed magnetic moment values. Infrared spectra, thermal analysis and molar conductivity values are in complete agreement with the proposed structure. The mono and dinuclear copper(II) complexes exhibit maximum fungitoxicity in comparison to the corresponding cobalt(II) and nickel(II) complexes.